C-CONFORMAL METRIC TRANSFORMATIONS ON FINSLERIAN HYPERSURFACE - Narasimhamurthy, S.K. (IndoMS, 2011)
The purpose of the paper is to give some relation between the originalFinslerian hypersurface and other C-conformal Finslerian hypersufaces. In this pa-per we dene three types of hypersufaces, which were called a hyperplane of the 1stkind, hyperplane of the 2nd kind and hyperplane of the 3rd kind under considerationof C-conformal metric transformation.DOI :Â http://dx.doi.org/10.22342/jims.17.2.2.59-66